Early Childhood Teachers’ Ability in Pronouncing Vocabularies - Lestiyanawati, Rochyani; Alawiyah, Luluk (Journal of Language Intelligence and Culture, 2020)
Problems for learners of English as Foreign Language may appear due to the lack of English mastery of the teachers. Since teachers are regarded as input for language learning, it impacts the students’ achievement. Pronunciation is one of the problems faced by both Indonesian teachers and students. When the teachers give the correct pronunciation, it results in the correct pronunciation of the students. On the other hand, the wrong pronunciation of the teachers will impact the students’ incorrect pronunciation. This study is aimed to reveal the early childhood teachers’ ability in pronouncing English vocabulary. The findings of the study are to determine the appropriate treatment which might be needed to overcome the problems. The subject of the study were 40 randomly selected early childhood teachers. The data were collected by testing their vocabulary mastery and pronunciation ability. The result of the study showed that the English mastery of early childhood teachers was needed to be developed for less ability in pronouncing the vocabulary correctly. The questionnaires also implied that the teachers need improvement in dealing with English.